PTH-104 Prevalence of genetic haemochromatosis gene mutations in patients with coeliac disease. (23rd September 2015) - Salunke, S S; Lightbody, E; Morgan, A; Nicol, A; Kelly, J; Cooke, A; Morris, A J; Forrest, E H; Gillespie, R; Winter, J; Gaya, D R; Cahill, A; et al.
Abstract : Introduction: Genetic haemochromatosis (GH) and Coeliac disease (CD) are both common conditions in people of North European/or Celtic decent with a high prevalence in Scotland. Aim: To assess the prevalence of GH gene mutations in patients with CD and compare with local controls, and examine whether the presence of GH mutations is associated with an older age of diagnosis of CD. Methods: Following ethical approval, patients with CD attending Gastroenterology clinics at Glasgow Royal Infirmary and Stobhill Hospitals were recruited into the study. Each patient had blood taken for C282Y and H63D gene mutation analysis in addition to standard bloods at clinic. The samples were anonymised but split into those from patients <45 years (group A) and those >45 years (group B). The mutation results were analysed for carrier and mutation frequency. The results were compared to 340 local controls anonymously tested for GH mutations as part of larger genetic disease prevalence screening programme. Results: 138 patients were recruited (A=59, B=79). The C282Y carrier frequency was 1 in 6.0 among CD patients compared to 1 in 8.1 among controls (NS). C282Y and H63D mutation frequencies were 8.1% and 14.5% in CD patients compared with 6.2% and 15.5% in controls (NS). There was no difference in mutations frequencies between CD patients diagnosed younger or older than 45 years old: 16.9% vs 16.5% for C282Y mutations, and 35.6% vs 24.1% for H63D. Conclusion: The frequency of GH mutations in CD is similar to that in the local population. The presence of these mutations does not appear to delay the diagnosis of CD.